Ependymoma - Milde, Till; Witt, Olaf; Pfister, Stefan; Witt, Hendrik (Molecular Pathology of Nervous System Tumors, 2015)
Brain tumors are the most common childhood solid malignancy and the leading cause of cancer-related mortality in children. Ependymomas are among the most prevalent entities in children and show a...